2021
DOI: 10.3389/fpsyt.2021.559154
|View full text |Cite
|
Sign up to set email alerts
|

Tutor of Resilience: A Model for Psychosocial Care Following Experiences of Adversity

Abstract: This article describes a model for training service providers to provide interventions that build resilience among individuals who have experienced adversity. The Tutor of Resilience model emphasizes two distinct dimensions to training: (1) transforming service providers' perceptions of intervention beneficiaries by highlighting their strengths and capacity for healing; and (2) flexibly building contextually and culturally specific interventions through a five-phase model of program development and implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…In conclusion, previous studies have stated that resilience factors may function as both compensatory factors (i.e., decreasing negative outcomes; Giordano et al, 2020) and protective factors (i.e., modulating or diminishing the impact of adversity and difficulty; Giordano et al, 2019, 2021; Giordano & Ungar, 2021). Results of our studies show that family resilience supported individuals' well‐being during the COVID‐19 pandemic, as both a compensatory factor—reducing parents' perceptions of their children's behavioral impairments—and a protective factor—alleviating the relationship between the severity of the caregiver's stress and children adjustment, as perceived by parents.…”
Section: Discussionmentioning
confidence: 67%
“…In conclusion, previous studies have stated that resilience factors may function as both compensatory factors (i.e., decreasing negative outcomes; Giordano et al, 2020) and protective factors (i.e., modulating or diminishing the impact of adversity and difficulty; Giordano et al, 2019, 2021; Giordano & Ungar, 2021). Results of our studies show that family resilience supported individuals' well‐being during the COVID‐19 pandemic, as both a compensatory factor—reducing parents' perceptions of their children's behavioral impairments—and a protective factor—alleviating the relationship between the severity of the caregiver's stress and children adjustment, as perceived by parents.…”
Section: Discussionmentioning
confidence: 67%
“…R2 is a multisystemic resilience‐oriented approach which helps healthcare leaders strengthen access to personal and organizational resources. Implementation of the R2 model is intended to address the following three generalized principles to build a resilient healthcare organization: Applying a participatory approach to program design which integrates providers' perceptions of possible solutions to complex problems (Giordano et al., 2021 ; Giordano & Ungar, 2021 ). In order to identify practices that support organizational and healthcare workers' resilience, the R2 program involved healthcare leaders in selecting the rugged qualities and resources most likely to build resilience in their particular settings during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Applying a participatory approach to program design which integrates providers' perceptions of possible solutions to complex problems (Giordano et al., 2021 ; Giordano & Ungar, 2021 ). In order to identify practices that support organizational and healthcare workers' resilience, the R2 program involved healthcare leaders in selecting the rugged qualities and resources most likely to build resilience in their particular settings during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that families during the COVID-19 pandemic find within themselves a source of resilience to cope with multiple stresses, adapt to devastating dislocations, strengthen important bonds, endure uncertainty, and manage future challenges [ 5 ]. In particular, studies conducted on children exposed to adversities have shown the need for mutual support, comfort, and protection when helplessness and confusion are widespread [ 29 , 30 , 31 , 32 ]. Children learn coping strategies either directly, e.g., when parents encourage their children to use specific techniques to cope with stressors or their reactions to them [ 33 ], or indirectly, e.g., when children observe their parents’ emotional, cognitive, and behavioural strategies for coping with stressful events [ 18 , 34 ].…”
Section: Discussionmentioning
confidence: 99%